THE EFFECT OF CHARACTERISTICS OF LOCAL GOVERNMENTS AND BPK AUDIT OPINIONS ON FINANCIAL PERFORMANCE OF LOCAL GOVERNMENTS (Empirical Study on Regencies/Cities in Papua Province in 2018-2019) - Abner SP Marlissa; Siti Rofingatun; Rudiawie Larasati (Jurnal Akuntansi dan Keuangan Daerah, 2021)
This study aims to determine the effect of Wealth Level, Dependency Level and Audit Opinion on Financial Performance. The independent variables in this study are the level of wealth, the level of dependence and audit opinion and the dependent variable is the financial performance. The population in this study was a total of 30 Regency/City Regional Governments of Papua Province who were recorded in the Financial Audit Agency for the 2018-2019 period. The sample in this study is the number of audit results reports at the Papua Province Regency/City Financial Audit Agency for the 2018-2019 period. The type of data in this study is quantitative data. The source of data used in this study is secondary data in the form of financial statements in 2018 to 2019 obtained from the Financial Audit Agency (BPK). Data analysis used descriptive statistics, classical assumption test, multiple analysis, and hypothesis testing. Results Based on the research shows that partially and simultaneously the Regional Wealth Level Audit, Dependence Level and Opinion have a significant effect on Financial Performance. This significant effect indicates that the expected hypothesis can be accepted. The significant hypothesis explains that a high level of regional wealth, dependence and audit opinion can increase the number of distributions of financial performance.